Probiotics in the non-surgical treatment of periodontitis: a systematic review and network meta-analysis - Carlota Duarte de Mendonça; António Duarte Sola Pereira da Mata; Luís Filipe Ribeiro Azevedo; Joana Faria Marques; João Miguel Lourenço Silveira; Duarte Nuno da Silva Marques (BMC, 2024)
Abstract This systematic review and network meta-analysis aimed to assess the impact of combining professional mechanical plaque removal (PMPR) with probiotics compared to PMPR + placebo on probing pocket depth (PPD) and clinical attachment level (CAL). Randomized controlled trials published until November 2023 were searched across electronic databases, peer-reviewed journals, and grey literature. Two authors independently selected, extracted data, and assessed bias risk. Primary outcomes were mean changes in PPD and CAL. Secondary outcomes included mean changes in bleeding on probing (BOP), plaque index, and colony-forming units. Network meta-analysis with the frequentist weighted least squares approach evaluated the data quantitatively, and CINeMA framework evaluated the quality of evidence. In 33 articles involving 1290 patients, results were stratified by follow-up period (short and long-time studies) and sensitivity analyses conducted based on probiotic therapy duration (1 month reference). Network meta-analysis revealed significant mean differences in PPD for nine probiotic interventions, CAL for eighteen interventions, and BOP for eight interventions, with Lactobacillus demonstrating the most substantial effects. Combining PMPR with probiotics as adjuvants to subgingival instrumentation may be more effective in improving PPD and CAL. Lactobacillus emerged as the most comprehensive and effective among the studied probiotic.